ARKEOLOGI PENGETAHUAN MICHEL FOUCAULT DALAM NOVEL “MISTERI SUSTER ANGGRAINI” KARYA HENRI NURCAHYO - Sahrul Sabilillah; Sunu Catur Budiyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Shifts in power structures and social thought have influenced the formation of knowledge and the concept of truth throughout history. Literature serves as a medium that reflects these changes. Henri Nurcahyo’s Misteri Suster Anggraini portrays the struggle of knowledge within dominant social discourses. This study aims to describe the processes of knowledge deconstruction and reconstruction in the novel using Michel Foucault’s Archaeology of Knowledge. A descriptive qualitative method with a library research approach was employed. The data consisted of words, phrases, and sentences representing knowledge structures, which were analyzed to identify changes in discourse and perspectives. The findings reveal that knowledge deconstruction is reflected in the novel’s critique of established truths and its exposure of marginalized historical narratives. Knowledge reconstruction emerges through the reinterpretation of fragmented information into a more critical perspective. The study concludes that the novel functions not only as a literary work but also as a representation of the transformation of knowledge and human perspectives within social reality.